Design and development of a density meter - Sin, Gek Kwee. (2008)
This project involves the design and development of a density meter using 80C196KC Intel micro-controller. The Archimedes' principle was applied in determining the density of the solid substance of interest. Previous work done by EEE and MPE FYP was reviewed. The circuits mentioned in the MPE report used for interfacing the micro-controller with the weighing balance, solenoid valve, and sensors were tested and additional features were added to improve the usability of the density meter. The program for controlling the product was written in C language. Mechanical parts were designed to accommodate the PCBs and the components. The interfacing circuits and mechanical parts were then fabricated using NC machines and SLS technology respectively. Shortcomings of the previous design were identified and overcome. Physical dimension of (197x298x220)mm3 was achieved. The assembled prototype was tested using four materials of different densities. The data was analysed and an average accuracy of 95 % was obtained. Recommendations were also made for further improvement.